THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE TO CORPORATE FINANCIAL PERFORMANCE (Empirical Study of the Companies that always Listed on SRI KEHATI Index during the Period 2010-2014) - Kurniawan, Bonifasius Dian Dwi; Wibowo, Alexander Jatmiko (Modus Journals, 2017)
AbstractÂ The purpose of this research is to examine if there exists any systematic relation between corporate social responsibility (CSR) and corporate financial performance (CFP). The research samples are 16 companies that always listed in SRI KEHATI Index during period 2010-2014. The research uses purposive sampling method, regressed and descriptive analysis.CSR is measured by Corporate Social Responsibility Disclosure Index (CSRDI), whereas CFP is measured by return on assets (ROA), Return on Equity (ROE) and Price to Book Value (PBV). The research indicates CSR has positive influence to financial performance measured with financial ratios such as ROA, ROE and PBV. These results are robust across different measures of variables.Â Keywords: Corporate Social Responsibility (CSR), Corporate Financial Performance (CFP), Return on Asset (ROA), Return on Equity (ROE), Price to Book Value (PBV).